2015
DOI: 10.1007/jhep10(2015)004
|View full text |Cite
|
Sign up to set email alerts
|

A N = 2 $$ \mathcal{N}=2 $$ supersymmetric AdS4 solution in M-theory with purely magnetic flux

Abstract: We find a new N = 2 AdS 4 solution in M-theory supported by purely magnetic flux via a sequence of abelian and non-abelian T-dualities. This provides the second known example in this class besides the uplift of the Pernici and Sezgin solution to 7d gauged supergravity constructed in the eighties. We compute the free energy of the solution, and show that it scales as N 3/2 . It is intriguing that even though the natural holographic interpretation is in terms of M5-branes wrapped on a special Lagrangian 3-cycle,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 91 publications
2
21
0
Order By: Relevance
“…In order to study similarities and differences we suggest to study the backgrounds found in [17,25,31,34,[37][38][39]. These seem to be the natural candidates given their isometries.…”
Section: Jhep01(2018)071mentioning
confidence: 99%
“…In order to study similarities and differences we suggest to study the backgrounds found in [17,25,31,34,[37][38][39]. These seem to be the natural candidates given their isometries.…”
Section: Jhep01(2018)071mentioning
confidence: 99%
“…These works have widely applied non-Abelian T-duality to generate new AdS backgrounds of relevance in different contexts. While some of the new solutions avoid previously existing classifications [11,28,31,32], which has led to generalizations of existing families [38][39][40][41], some others provide the only known explicit solutions belonging to a given family [32,33], which can be used to test certain conjectures, such as 3d-3d duality [42,43]. Some of these works also put forward some ideas to define the associated holographic duals.…”
Section: Jhep09(2017)038mentioning
confidence: 99%
“…In this work we present some further examples. Interesting solutions generated this way 6 are the only explicit AdS 6 solution to Type IIB supergravity constructed in [37] 7 and the recent N = 2 AdS 4 solution to M-theory with purely magnetic flux constructed in [42], which provides the only such explicit solution besides the Pernici-Sezgin background derived in the eighties [43]. Both these solutions may play an important role as gravity duals of, respectively, 5d fixed point theories arising from Type IIB brane configurations, probably from 7-branes as in [44] (see [45]), and of 3d SCFTs arising from M5-branes wrapped on 3d manifolds in the context of the 3d-3d correspondence [46].…”
Section: Jhep08(2015)121mentioning
confidence: 99%